Catalytic Asymmetric Synthesis of α-Arylpyrrolidines and Benzo-fused Nitrogen Heterocycles - Dai, Xi-Jie (Angew Chem Int Ed Engl, 2019)
Herein we report a practical two-step synthetic route to α-arylpyrrolidines consisting of Suzuki-Miyaura cross-coupling and enantioselective copper-catalyzed intramolecular hydroamination reactions. The excellent stereoselectivity and broad scope for the transformation of substrates with pharmaceutically relevant heteroarenes render this method a practical and versatile approach for pyrrolidine synthesis. Additionally, this intramolecular hydroamination strategy facilitates the asymmetric synthesis of tetrahydroisoquinolines and medium ring dibenzo-fused nitrogen heterocycles.